Genome sequence of the Lebeckia ambigua-nodulating "Burkholderia sprentiae" strain WSM5005T. Issue 2 (September 2013) - Reeve, Wayne; Meyer, Sofie; Terpolilli, Jason; Melino, Vanessa; Ardley, Julie; Rui, Tian; Tiwari, Ravi; Howieson, John; Yates, Ron; O'Hara, Graham; Lu, Megan; Bruce, David; et al.
Abstract "Burkholderia sprentiae " strain WSM5005T is an aerobic, motile, Gram-negative, non-spore-forming rod that was isolated in Australia from an effective N2 -fixing root nodule ofLebeckia ambigua collected in Klawer, Western Cape of South Africa, in October 2007. Here we describe the features of "Burkholderia sprentiae " strain WSM5005T, together with the genome sequence and its annotation. The 7, 761, 063 bp high-quality-draft genome is arranged in 8 scaffolds of 236 contigs, contains 7, 147 protein-coding genes and 76 RNA-only encoding genes, and is one of 20 rhizobial genomes sequenced as part of the DOE Joint Genome Institute 2010 Community Sequencing Program.